Interpreting Reservoir Permeabilities from Wireline Formation Test Data - Du, H.; Liu, Y.; Li, X.; Guan, F.; Sui, X. (Petroleum science and technology, 2013)
In order to provide accurate permeabilities of reservoirs for productivity estimate in offshore oil fields, in this study a semianalytical model of unsteady ellipsoidal flow and a numerical simulation algorithm have been developed to interpret wireline formation test data. The model is derived from basic principles of fluid mechanics in porous medium, and the time variation of test flows and anisotropy of formations are both taken into account. The approaches had been applied successfully to interpreting the test data of a new pumpout wireline formation tester, and the results show the validity of the new method presented.